2015
DOI: 10.3233/thc-151088
|View full text |Cite
|
Sign up to set email alerts
|

Body posture recognition and turning recording system for the care of bed bound patients

Abstract: This paper proposes body posture recognition and turning recording system for assisting the care of bed bound patients in nursing homes. The system continuously detects the patient's body posture and records the length of time for each body posture. If the patient remains in the same body posture long enough to develop pressure ulcers, the system notifies caregivers to change the patient's body posture. The objective of recording is to provide the log of body turning for querying of patients' family members. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The articles that were included in our analysis were published between 2007 and 2020 and were undertaken in the United States [25][26][27][28][29][30][31][32][33][34][35], China [36][37][38][39][40][41][42][43][44], Spain [45][46][47][48][49][50], Japan [51,52], Italy [53,54], Korea [55], and Greece [56]. According to the applied area of the included studies, we divided the articles into three components: predictive model (12 studies), posture recognition (11 studies), and image analysis (9 studies).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The articles that were included in our analysis were published between 2007 and 2020 and were undertaken in the United States [25][26][27][28][29][30][31][32][33][34][35], China [36][37][38][39][40][41][42][43][44], Spain [45][46][47][48][49][50], Japan [51,52], Italy [53,54], Korea [55], and Greece [56]. According to the applied area of the included studies, we divided the articles into three components: predictive model (12 studies), posture recognition (11 studies), and image analysis (9 studies).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In the case of falls, it is the sensory motion detection that is predominantly conclusive. However, nursing scientists have repeatedly reported that falls in the elderly can have causes attributed to multiple intrinsic and extrinsic factors [36,48,49]. A simple motion measurement cannot account for all this, of which professional caregivers are surely aware of.…”
Section: Underestimated Nursing Problemsmentioning
confidence: 99%
“…Other SeTe devices could be used in secret. For example, motionsensing mats [32] or carpets [33], SeTe devices under [32,34] or on an edge [35] of a mattress, under a bed sheet [36], or as a contact sensor [17] can easily be installed in secret. The question of whether SeTe surveillance could potentially be secretly installed was not discussed in any study.…”
Section: Technical Problems and Ethical Considerationsmentioning
confidence: 99%
“…Nursing homes and hospitals use set programs to avoid the development of bed-sores in bedridden patients, such as pressure-shifting on a regular basis and using cushions with pressure-relief components. The sleeping posture of bed-bound patients needs to be regularly changed in order to reduce the risk of developing pressure ulcers [ 1 ], and bed sensor systems have been developed to recognize sleeping postures.…”
Section: Introductionmentioning
confidence: 99%
“…For bed-bound and limited-mobility patients, the sensor system employed is usually simple and inexpensive, but may achieve a high posture recognition accuracy when the patient is placed by the caregiver in the central axis of the bed. However, the accuracy drops acutely with deviation of the patient’s body from the central axis [ 1 , 10 ]. For ambulatory patients or healthy elderly people, the design becomes much more complicated and relatively more expensive, as human beings exhibit a variety of postures during sleep.…”
Section: Introductionmentioning
confidence: 99%